The prognostic role of various indices and ratios of Doppler velocimetry in patients with pre-eclampsia. (February 2015) - Orabona, Rossana; Gerosa, Vera; Gregorini, Maria Elena; Pagani, Giorgio; Prefumo, Federico; Valcamonico, Adriana; Frusca, Tiziana
Abstract Doppler velocimetry is a non-invasive method to monitor pregnancies complicated by pre-eclampsia. We aimed to assess the predictive value of adverse perinatal or maternal outcome of three ratios, i.e. middle cerebral to umbilical arteries pulsatility indices (PI), middle cerebral to uterine arteries PI and uterine to umbilical arteries PI, compared with that of uterine and umbilical arteries PI in pre-eclamptic patients. This is a cohort study on 168 singleton pregnancies between January 2010 and June 2013. Doppler velocimetry was performed at the diagnosis of pre-eclampsia. Logistic regression analysis was performed and receiver-operating characteristics (ROC) curves were calculated to determine the predictive ability of each Doppler index. Multivariate analysis was run to adjust results for confounding parameters. Seventy-eight cases were complicated by adverse perinatal outcome, 79 by maternal one, 49 by both. Considering perinatal outcome, area under ROC curve was 0.730 for uterine arteries PI, 0.691 for umbilical artery PI and 0.834 for middle cerebral to uterine arteries PI ratio, while for maternal one 0.720 for uterine arteries PI, 0.686 for umbilical artery PI and 0.817 for middle cerebral to uterine arteries PI ratio. At multivariate analysis, only middle cerebral to uterine arteries PI ratio remain statistically significant for both outcomes (p = 0.001). The cited ratio appeared more accurate than all other considered indices in predicting perinatal and maternal outcomes in patients affected by pre-eclampsia.